Maximizing Entrepreneurship learning/training benefits - OUKIL, M-Said (Journal of Finance & Corporate Governance, 2017)
As an educator who strives for highest quality university teaching, I do my best to create a complete immersion of my students in learning from theory, best practices, real examples and a great variety of in- and out- of university and class activities. Hence, my approach in teaching entrepreneurship courses in particular, consists of providing with every possible tip to make learning cognitive, fun, closest to reality and effectively productive and promising. Believing in the fundamental link or relationship, between innovation and entrepreneurship, I do focus very much on stimulating creativity through individual and team-based assignments, as well as games and picture-based exercises. Problem-solving games and exercises are particularly used. A best expected outcome in my entrepreneurship courses is a choice for enrolled students to create either a spin-off company, or a sound business plan to implement after graduation, individually or collectively. A major policy implication is the need for great improvements in courses content and teaching methods.